Wage Losses and Inequality in Developing Countries: labor market and distributional consequences of Covid-19 lockdowns in Turkey - Anil Duman (Global Labor Organization (GLO), 2020)
We develop a possibility to work index (PWI) taking the ability to work from home and workplace closures into account. By using the data from the HLFS in Turkey, we examine the individual level determinants of PWI. Our findings reveal that PWI and ability to work from home are significantly different, and essential or closed jobs are not necessarily concentrated at the bottom of the wage distribution. Therefore, from a policy perspective, PWI can be a more encompassing measure of risk and can assist the public authorities to design better targeted social policies. Our results also point out that wage inequality is likely to deteriorate as a result of the supply shocks from confinement policies. However, the overall negative distributional effects of lockdown and disparity between employees in different economic activities become more substantial with duration. These suggest that in order to avoid major increases in earning inequalities and related social problems, governments would be better off with shorter and stricter lockdowns.
Keywords: D33; E24; J21; J31; 330; workplace closures; wage loss; wage inequality; teleworking; developing countries